Multiple microRNA regulation of lipoprotein lipase gene abolished by 3′UTR polymorphisms in a triglyceride-lowering haplotype harboring p.Ser474Ter. (March 2016) - Caussy, Cyrielle; Charrière, Sybil; Meirhaeghe, Aline; Dallongeville, Jean; Lefai, Etienne; Rome, Sophie; Cuerq, Charlotte; Euthine, Vanessa; Delay, Mireille; Marmontel, Oriane; Di Filippo, Mathilde; Lagarde, Michel; et al.
Abstract: Background: Lipoprotein lipase (LPL) is a key enzyme in triglyceride (TG) metabolism. LPL gene single nucleotide polymorphisms (SNPs) are associated with TG concentrations however the functionality of many of these SNPs remains poorly understood. MicroRNAs (miR) exert post-transcriptional down-regulation and their target sequence on the 3′UTR may be altered by SNPs. We therefore investigated whether LPL 3′UTR SNPs could modulate plasma TG concentration through the alteration of miR binding-sites. Methods and results: We performed genetic association studies of LPL 3′UTR SNPs with TG concentrations in 271 type 2 diabetic patients and in general population samples (2997 individuals). A specific LPL haplotype (Hap4) was associated with lower plasma TG concentration (TG-0.18, IC95% [−0.30, −0.07] mmol/L or logTG-0.13, IC95% [−0.18, −0.08], p = 4.77·10 −8 ) in the meta-analysis. Hap4 comprises seven 3′UTR SNP minor alleles and p.Ser474Ter (rs328) a well-documented nonsense mutation associated with low TG concentration although by an unknown mechanism so far. Bio-informatic studies identified several putative miRNA binding-sites on the wild-type Hap1 haplotype, lost on Hap4. Functional validation performed in HEK-293T cells using luciferase expression constructs with various LPL 3′UTR allele combinations demonstrated a binding of miR-29, miR-1277 and miR-410 on Hap1, lost on Hap4. This loss of specific miR binding-site in presence of Hap4 was independent of the allelic variation of p.Ser474Ter (rs328). Conclusions: We report the regulation of LPL by the miR-29, miR-1277 and miR-410 that is lost in presence of Hap4, a specific LPL TG-lowering haplotype. Consequently p.Ser474Ter association with TG concentration could be at least partially explained by its strong linkage disequilibrium with these functional 3′UTR SNPs. Highlights: A LPL 3′UTR haplotype (Hap4) is associated with lower triglyceride concentrations. This LPL Haplotype 4 induces a loss of several functional microRNA binding sites. The p.Ser474Ter hypoTG effect could be due to its linkage disequilibrium with Hap4.